2010
DOI: 10.1093/ndt/gfq321
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin is not useful as a biomarker for iron needs in haemodialysis patients on maintenance erythropoiesis-stimulating agents

Abstract: Although our study suggests an important role for hepcidin in regulating iron homeostasis in HD patients on ESA, our findings do not support its utility as a predictor of iron needs, offering no advantage over established markers of iron status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
68
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 35 publications
9
68
0
3
Order By: Relevance
“…CHD patients with sustained hyperhepcidinemia may be good candidates for the use of hepcidin antagonists [4] promote proper iron utilization for erythropoiesis. Available studies on hepcidin level as a guide to intravenous iron supplementation in CHD are limited to the observation of a lack of correlation with hemoglobin increase in relatively small and unselected populations [17]. However, the subgroup of CHD patients with repeatedly normal to low serum hepcidin levels may represent the ideal target for safe and effective iron supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CHD patients with sustained hyperhepcidinemia may be good candidates for the use of hepcidin antagonists [4] promote proper iron utilization for erythropoiesis. Available studies on hepcidin level as a guide to intravenous iron supplementation in CHD are limited to the observation of a lack of correlation with hemoglobin increase in relatively small and unselected populations [17]. However, the subgroup of CHD patients with repeatedly normal to low serum hepcidin levels may represent the ideal target for safe and effective iron supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the relatively larger study (n = 56) did not show hepcidin as a useful predictor of hemoglobin response to i.v. iron [17]. However, this study had some limitations like possible underpowering and lack of a control group, so that larger trials comparing hepcidin-driven to standard therapeutic approaches are eagerly awaited.…”
Section: Potential Clinical Usefulness Of Hepcidin Determination In Cmentioning
confidence: 99%
“…Interestingly, these smaller hepcidin isoforms occur only in serum of patients with diseases that are associated with increased concentrations of hepcidin-25, such as acute myocardial infarction (AMI), 4 sepsis, anemia of chronic disease (ACD), metabolic syndrome, and chronic kidney disease (CKD) ( Fig. 2) (12)(13)(14)(15)(16)(17). In vivo studies in mice have demonstrated that only full-length 25 amino acid hepcidin induces significant hypoferremia when injected intraperitoneally (18 ).…”
mentioning
confidence: 99%
“…Other laboratory markers have been investigated to improve the sensitivity and specificity of the detection of this condition, including serum transferrin receptor, percentage hypochromic RBCs, and reticulocyte hemoglobin content [18]. In the context of nephrology, measurement of the percentage of hypochromic RBCs in the blood has generally been found to be the optimal test, followed by reticulocyte hemoglobin content [19,20]. Serum transferrin receptor is of less value in the CKD setting, because many patients are on erythropoietin-like drugs, and enhanced erythropoiesis is one of the factors evoking an increase in serum transferrin receptor, confounding its use as a marker of iron insufficiency.…”
Section: Absolute and Functional Iron Deficiencymentioning
confidence: 99%
“…iron. Measurement of serum hepcidin has been suggested as a potential alternative in this regard, although there have been recent concerns about its variability in hemodialysis patients [59] and whether or not it is in fact any better than measurement of hypochromic RBCs [20].…”
Section: Guidelines Regardingmentioning
confidence: 99%